OPTIMALISASI KERJA PRAKTIK DALAM MENINGKATKAN KOMPETENSI MAHASISWA PADA PHINTRACO SEKURITAS PONTIANAK - Mardeni Mardeni; Dedy Dedy (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2026)
The internship program is an educational strategy to integrate theory with practice in the industrial world. The internship activity at Phintraco Sekuritas Pontianak aims to develop students' technical and non-technical skills. Based on the implementation of the internship, students acquired technical skills such as creating activity letters, drafting proposals for fund assistance requests from the Indonesia Stock Exchange (IDX), designing posters, as well as understanding stocks and technical analysis. Furthermore, soft skills such as discipline, effective communication, creativity, and teamwork also experienced significant improvement. Educational activities for the younger generation about capital market investment are also an important part of this internship. Thus, the internship at Phintraco Sekuritas Pontianak becomes valuable preparation for students in facing the real world of work.